Nanotecnologia na terapia de doenças neurodegenerativas: Alzheimer e Parkinson - Castro, Juliane Souza de (Brasil, 2024)
Neurodegenerative diseases, such as Alzheimer's and Parkinson's, have represented a growing challenge to global public health. The increase in life expectancy emphasizes the urgency for innovative and effective therapeutic approaches. Nanotechnology emerges as a promising area leading this fight, offering potentially revolutionary solutions. Traditional therapies face significant difficulties, such as the inability to cross the blood-brain barrier (BBB) and the lack of specificity in targeting therapies to affected sites in the brain, resulting in reduced efficacy and adverse side effects. This work aims to evaluate, through an integrative review, the potential and effectiveness of nanotechnologies applied in therapies for Alzheimer's and Parkinson's diseases. Studies highlight that nanoparticles, such as liposomes, dendrimers and polymeric nanoparticles, offer significant advances in drug delivery to the brain, improving bioavailability and therapeutic efficacy. Functionalized liposomes and poly-lactic-co-glycolic acid (PLGA) nanoparticles have shown promise in sustained drug release and crossing the BBB. Nanotechnology has the potential to transform the treatment of neurodegenerative diseases, offering new possibilities for precise drug delivery and overcoming limitations of traditional therapies. The findings highlight the importance of nanotechnology in evolving therapeutic approaches for Alzheimer's disease and Parkinson's disease, paving the way for more effective and less invasive treatments.